Bluetooth host-side protocol stack development using formal design techniques - Caccam, Anne Margrette Q.
Bluetooth is a wireless technology standard for the interconnection of electronic devices in the personal space. It started out as a cable replacement technology and became a wireless personal networking (WPAN) solution. This paper describes the development of a Bluetooth Host-side Protocol Stack using Object-oriented and Formal Design Techniques such as SDL, ASN.1 and MSC. This marks the initial effort of the Advanced Science and Technology Institute in developing a complete System on a Chip (SOC) solution within five years time.
Keywords: Bluetooth; WPAN; Communications Protocol Software; SDL